Estabelecimento de medidores moleculares envolvidos no processo de infecção de paracoccidioides brasiliensis em celulas de mamifero in vitro. - Francisco Laurindo da Silva (2004)
Very little is known about the early events in the interaction between Paracoccidioides brasiliensis cells and its host. In order to unveil the role of carbohydrates, peptides and self-produced molecules on the mechanisms of interaction between the fungus and epithelial cell in culture, we analyzed the effect of Sorbitol, D-mannoese, D-fucose, N-acetyl-glucosamine, D-glucosamine, Fructose and D-galactosamine, the peptides GRDSPK, GRGDTP e GRDGS and culture supemadant on the adhesion of P. brasiliensis yeast cells to CCL-6 cells on culture. The fungal cells were cocultivated with the epithelial cell line and different concentrations of the interaction. Six hours after the treatment the cells were fixed and observed on light microscopy. The number of P. brasiliensis cells adhered to the CCL-6 monolayer was estimated. D-fucose, N-acetyl-gçicpsa,ome. D-mannose, D-glucosamine and D-galactosamine treatments diminished the number of adhesion events if compared to the observed with untreated controls. Sorbitol and Fructose treated cells had the same adhesion behavior as the observed in the controls. In order to detect the presence of carbohydrates in the fungus surface, P. brasilienssis propagules were treated with fluorescent lectins. WGA-FITC and Con-A-FITC lectins labeled P.brasiliensis cells while SBA and PNA lectins did not bind to the yeast cell. The peptides GRDSPK, GRGDTP also diminished the number of adhesion events observed and antibodies against 111 and 2 integrins labeled P. brasiliensis cells. Old RPMI culture supernadant of P. brasiliensis also diminished the adhesion events of the fungus on CCL-6 cells. The molecule responsible for such effect is unknown, but is thermostable and non-proteic.